2009
DOI: 10.1158/1078-0432.ccr-08-2663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Efficacy of Recombinant Human Interleukin-21 in Patients with Stage IV Malignant Melanoma without Prior Treatment: A Phase IIa Trial

Abstract: Purpose: Human interleukin-21 (IL-21) is a class I cytokine that mediates activation of CD8 + T cells, natural killer (NK) cells, and other cell types. We report final clinical and biological results of a phase II study of recombinant human IL-21 (rIL-21) in patients with metastatic melanoma. Experimental Design: Open-label, single-arm, two-stage trial. Eligibility criteria: unresectable metastatic melanoma, measurable disease by Response Evaluation Criteria in Solid Tumors, no prior systemic therapy (adjuvant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 46 publications
4
111
0
1
Order By: Relevance
“…When NK cells are adoptively transferred or activated in situ by cytokines, their clinical utility in selected malignancies, such as acute myeloid leukemia and malignant melanoma, is becoming apparent (3)(4)(5). Haploidentical NK cells can persist and expand in vivo and may have a role in the treatment of selected malignancies used alone or as an adjunct to hematopoietic stem cell transplantation (6).…”
mentioning
confidence: 99%
“…When NK cells are adoptively transferred or activated in situ by cytokines, their clinical utility in selected malignancies, such as acute myeloid leukemia and malignant melanoma, is becoming apparent (3)(4)(5). Haploidentical NK cells can persist and expand in vivo and may have a role in the treatment of selected malignancies used alone or as an adjunct to hematopoietic stem cell transplantation (6).…”
mentioning
confidence: 99%
“…Such qualities make IL-21 a suitable agent for immunotherapy especially in conditions such as HIV, Chronic Hepatitis renal cell carcinoma, melanoma and non hodgkin's lymphoma, where a sustained and potent immune response is necessary to keep pathogens at bay (Thompson et al, 2008;Davis et al, 2009;Yi et al, 2009;Yue et al, 2010;Timmerman et al, 2012). IL-21 like IL-15 is also unique among the common γchain family of cytokines in its ability to maintain CD8 T cell population without causing any activation induced cell death (Moroz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Results from these trials have also shown the cytokine to be well tolerated with an increase in NK and CD8 C T cell function through increased IFNg and perforin production. 104,105 Despite these effects on CD8 C T and NK cells, IL-21 has been shown to inhibit DC activation and maturation and induces apoptosis of these cells via STAT3 signaling. 107,108 Thus IL-21 is detrimental toward DC function.…”
Section: Il-21mentioning
confidence: 99%